Paradoxical Role of Self-Control in Generation Z Blind Box Impulsive Buying - Sinta Putri Nabila; Budi Prasetiyo (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study examined the effects of Fear of Missing Out (FOMO), electronic word-of-mouth (eWOM), and hedonic value on the impulsive buying of Blind Box products among Generation Z, with self-control as a moderator. A quantitative survey of 385 Generation Z TikTok users in Bandung who had purchased Blind Box products was conducted from January to March 2026, yielding 385 valid responses (100% response rate), analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that FOMO (β=0.268, p<0.001), eWOM (β=0.323, p<0.001), and hedonic value (β=0.231, p < 0.001) positively and significantly influenced impulsive buying. Self-control also had a small but significant positive direct effect on impulsive buying (β=0.098, p=0.041) and positively moderated the relationships between FOMO, eWOM, and Hedonic Value with impulsive buying, revealing a paradoxical effect that contrasted with conventional assumptions about self-control. This study contributes to the development of the stimulus-organism-response theory and offers insights into consumer behavior in social commerce. The findings were limited to Generation Z consumers in Bandung and may not be generalized to other populations.